2023
DOI: 10.14710/nmjn.v13i1.48708
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management and Relating Factors among Chronic Kidney Disease Patients on Hemodialysis: An Indonesian Study

Abstract: Background: The latest approach to managing chronic kidney disease (CKD) involves the implementation of self-management methods. Nonetheless, numerous previous studies indicate that self-management behaviors remain inadequate among hemodialysis patients in Indonesia. Therefore, a deeper comprehension of the factors that affect a patient’s self-management should be studied.Purpose: This study aimed to examine self-management among CKD patients undergoing hemodialysis and its relating factors.Methods: The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Patients with chronic kidney disease who were well-educated about their health also adhered to their medications more consistently. An earlier study revealed that knowledge and education substantially predicted the selfmanagement score (Mailani et al, 2023).…”
Section: Discussionmentioning
confidence: 95%
“…Patients with chronic kidney disease who were well-educated about their health also adhered to their medications more consistently. An earlier study revealed that knowledge and education substantially predicted the selfmanagement score (Mailani et al, 2023).…”
Section: Discussionmentioning
confidence: 95%
“…6,17 Nurses play a significant role in providing holistic care to haemodialysis patients, addressing not only their physical needs but also their emotional and spiritual well-being. 7,18 Addressing haemodialysis patients' spirituality in nursing care is an essential component of high-quality care and these patients wanted nephrology nurses to incorporate spirituality into their care by such means as supporting and maintaining their religious and spiritual resources and connections. 19 Studies have shown that nurses are essential in providing support, maintaining religious and spiritual resources and establishing connections with patients, which can positively impact the patients' motivation to continue their treatment.…”
Section: Samplementioning
confidence: 99%
“…End-Stage Renal Disease (ESRD) is a medical condition characterized by the impaired functioning of the kidneys (Mailani et al, 2023). The prevalence of ESRD has been consistently increasing, with an estimated annual growth rate of approximately 6% to 8%, as indicated by the 2017 research conducted by Coresh.…”
Section: Introductionmentioning
confidence: 99%